Uteslutningens politiska ekonomi. Mot en transatlantisk konvergens? (Sociologisk Forskning, 2001)
Political economies of exclusion: Transatlantic convergence or transatlantic split?The paper takes its point of departure in a discussion of US American theories on poverty, race and ethnic divisions of labour which have influenced current European research on poverty and social exclusion among immigrants and new ethnic minorities with immigrant background. The focus is in particular on theories of the Black US urban ghetto and its workless and welfare dependent poor and on seemingly divergent theories on the dualisation of the so-called “global city”, new immigration and the new working poor. Their explanatory value is debated seen in relation to the development of the United States since the mid 1970s and the question of which demands to place on a more comprehensive and synthesising model with explanatory potential in the complex reality of the European Union. This is an emerging social formation which in a number of respects is markedly unlike that of the United States, even though the racialisation and ethnification of a new spectre of social exclusion also poses one of the most urgent social issues on this side of the Atlantic.